Increasing capacity to deliver diabetes self‐management education: results of the DESMOND lay educator non‐randomized controlled equivalence trial. Issue 11 (26th May 2014) - Carey, M. E.; Mandalia, P. K.; Daly, H.; Gray, L. J.; Hale, R.; Martin Stacey, L.; Taub, N.; Skinner, T. C.; Stone, M.; Heller, S.; Khunti, K.; Davies, M. J.
Abstract Aim To develop and test a format of delivery of diabetes self‐management education by paired professional and lay educators. Methods We conducted an equivalence trial with non‐randomized participant allocation to a Diabetes Education and Self Management for Ongoing and Newly Diagnosed Type 2 diabetes (DESMOND) course, delivered in the standard format by two trained healthcare professional educators (to the control group) or by one trained lay educator and one professional educator (to the intervention group). A total of 260 people with Type 2 diabetes diagnosed within the previous 12 months were referred for self‐management education as part of routine care and attended either a control or intervention format DESMOND course. The primary outcome measure was change in illness coherence score (derived from the Diabetes Illness Perception Questionnaire‐Revised) between baseline and 4 months after attending education sessions. Secondary outcome measures included change in HbA1c level. The trial was conducted in four primary care organizations across England and Scotland. Results The 95% CI for the between‐group difference in positive change in coherence scores was within the pre‐set limits of equivalence (difference = 0.22, 95% CI 1.07 to 1.52). Equivalent changes related to secondary outcome measures were also observed, including equivalent reductions in HbA1c levels. Conclusion Diabetes education delivered jointly by a trained lay person and a healthcare professional educator with the same educator role can provide equivalent patient benefits. This could provide a method that increases capacity, maintains quality and is cost‐effective, while increasing access to self‐management education.